Angular scattering of an Airy beam light sheet by a concentric sphere. (November 2017) - Cao, Zhaolou; Zhai, Chunjie
Highlights: Scattering of Airy beam light sheet by a concentric sphere is numerically studied. Plane-wave spectrum method and Mie scattering theory are employed. The influences of various parameters are investigated. Abstract: Angular distribution of scattered light by a particle reveals information of its topology and refractive index, which has been proved to be an effective method to identify and characterize the particle. In this paper, numerical study on angular scattering of a polarized one-dimensional Airy beam light sheet by concentric spheres is presented. Plane-wave spectrum method is adopted to simplify the problem into classic Mie scattering problem, which significantly improves computational efficiency. The effects of size parameters, refractive index and position of concentric spheres and Airy beam radius on the angular distribution of scattered light are investigated. This paper provides theoretical results for light scattering measurement where Airy beam light sheet is employed for reducing effects of multiple scattering.